UKRAINIAN VILLAGE ON THE EVE OF STALIN’S COLLECTIVISATION: TO THE ALTERNATIVES OF HISTORICAL PROGRESS (Південний архів (історичні науки), 2023)
The purpose of the study is to set and clarify the problem of the existence (or non-existence) of an alternative to Joseph Stalin’s ‘socialist restructuring’ of agriculture in the socio-economic state of the pre-collective farming peasantry. Research methods. The research methodology is based on the principles of macro-historical and comparative approaches, combined with the method of alternative histories, which allowed us to identify new aspects of the problem of the Stalinist totalitarian regime’s unprecedented social experiment of restructuring society based on utopian ideas of building communism. The study results show that since the mid-nineteenth century, society has objectively faced the need for modernisation and, accordingly, restructuring of agriculture tradition and the transformation of a peasant into a farmer. Imperial capitalist industrialisation was carried out mainly at the cost of the peasantry and had an unacceptable social and phycological cost for society. The Bolsheviks imposed a utopian communist model of modernisation (in Soviet terminological tradition – socialist industrialisation, collectivisation and cultural revolution) on society, which was not accepted by significant communities, particularly by the peasantry. However, the Bolsheviks did not care. They proceeded from the concept of the «dictatorship of the proletariat», and coercion and terror were organic to them in implementing their policies. The article emphasises that the situation in the countryside was particularly dramatic during the new economic policy period, i. e. on the eve of Soviet modernisation. As a result of the temporary abandonment of the «communist assault» and the introduction of «state capitalism» in the 1920s, the peasantry experienced a kind of renaissance and new prosperity period. The countryside saw a revival of pre-industrial livelihood strategies: the naturalisation of economic life, a focus on consumption, and distancing from the authorities and the Soviet economy. In other words, there was a tendency towards a certain autarky. Accordingly, agricultural production grew exceptionally slowly, and its marketability and consumption of industrial goods declined. The peasantry did not economically and politically support the Bolshevik course of accelerated industrialisation and the Bolshevik version of modernisation in general. Conclusions. It is proved that in the specific historical conditions of Soviet Ukraine in the 1920s, there was no alternative to the new version of the communist modernisation project. It is emphasised that the study of Soviet history in the concept of alternatives has a great perspective, especially with regard to its key moments. This allows for a better understanding of the nature and consequences for post-Soviet countries of the attempt to implement the communist project.
Keywords: socialist modernisation, new economic policy, Ukrainian peasantry, collectivisation, alternative, Stalinism